Free Volumes and Their Influence on Disaccomodation of Magnetic Susceptibility - Nabiałek, M. (Acta Physica Polonica A, 2023)
In weak magnetic fields, there are changes in the arrangement of atoms, which are otherwise called magnetic relaxations. The exact phenomenon that will be investigated in this paper concerns the disaccomodation of magnetic susceptibility, which is one of the most frequently observed effects of magnetic lag. During this magnetic delay, there is a reorientation of the axes of pairs of atoms corresponding to two different energy levels. This energy is related to the energies of exchange and spin–orbit coupling. The paper presents the results of magnetic susceptibility disaccomodation and describes its influence on the relaxation time matching spectrum.